Guerre sainte dans le Cône sud latino-américain : pentecôtistes versus umbandistes - Alejandro Frigerio; Ari Pedro Oro (Journal de la Société des Américanistes)
Holy war in the Latinamerican Southern Cone: pentecostalism versus umbanda devotees. The article examines the conflicts that have developed between the Igreja Universal do Reino de Deus and practitioners of Afro-Brazilian religions in Brazil, Uruguay and Argentina. It is argued that the intensity of their struggle is related to the degrees of social visibility and legitimation that these religions enjoy in each society as well as to the extent of organization that Umbanda devotees have attained – the existence of a collective action frame emphasizing their civil rights being particularly important in this regard. The paper also takes into account the relevance of contextual variables that trascend both religious groups, highlighting the role of the dominant national narrative that prevails in each country. Since this historical narrative assigns a specific place to the different ethnic and religious minorities within the nation, it constitutes a cultural resource that may be mobilized to vindicate a group’s rights or to deny them to its opponents.